Boruto : Naruto next generations. Volume 3, My story!! - Kodachi, Ukyo, 1979-; Kishimoto, Masashi, 1974- (Viz Media LLC, 2018)
"Naruto was a young shinobi with an incorrigible knack for mischief. He achieved his dream to become the greatest ninja in his village, and now his face sits atop the Hokage monument. But this is not his story... A new generation of ninja is ready to take the stage, led by Naruto's own son, Boruto! Naruto and his allies have the upper hand on Momoshiki until he transforms into a more powerful form. Naruto and Sasuke will have to team up to stand any chance of toppling this ferocious foe, but is Boruto holding the key to victory?!" -- Publisher description.